2019
DOI: 10.1002/ecy.2666
|View full text |Cite
|
Sign up to set email alerts
|

The hydraulic efficiency–safety trade‐off differs between lianas and trees

Abstract: Hydraulic traits are important for woody plant functioning and distribution. Associations among hydraulic traits, other leaf and stem traits, and species’ performance are relatively well understood for trees, but remain poorly studied for lianas. We evaluated the coordination among hydraulic efficiency (i.e., maximum hydraulic conductivity), hydraulic safety (i.e., cavitation resistance), a suite of eight morphological and physiological traits, and species’ abundances for saplings of 24 liana species and 27 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
59
2
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 65 publications
(147 reference statements)
2
59
2
2
Order By: Relevance
“…; C. M. Smith‐Martin, C. L. Bastos, O. R. Lopez, J. S. Powers, and S. A. Schnitzer, unpublished data ), and by maintaining healthy water status and maintaining high hydraulic conductivity during the dry season (e.g., van der Sande et al., ), lianas are particularly well suited to take advantage of high dry‐season light availability. By contrast, trees appear to suffer more water stress (C. M. Smith‐Martin, C. L. Bastos, O. R. Lopez, J. S. Powers, and S. A. Schnitzer, unpublished data ) and have a more conservative hydraulic conductivity strategy than lianas (van der Sande et al., ), and thus trees may not be able to capitalize as well as lianas on the high dry season light. The ability of lianas to capitalize on high solar radiation while maintaining healthy water status may also explain their extremely high abundance in such high‐light areas as treefall gaps, forest edges, and young tropical forests (reviewed by Schnitzer ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; C. M. Smith‐Martin, C. L. Bastos, O. R. Lopez, J. S. Powers, and S. A. Schnitzer, unpublished data ), and by maintaining healthy water status and maintaining high hydraulic conductivity during the dry season (e.g., van der Sande et al., ), lianas are particularly well suited to take advantage of high dry‐season light availability. By contrast, trees appear to suffer more water stress (C. M. Smith‐Martin, C. L. Bastos, O. R. Lopez, J. S. Powers, and S. A. Schnitzer, unpublished data ) and have a more conservative hydraulic conductivity strategy than lianas (van der Sande et al., ), and thus trees may not be able to capitalize as well as lianas on the high dry season light. The ability of lianas to capitalize on high solar radiation while maintaining healthy water status may also explain their extremely high abundance in such high‐light areas as treefall gaps, forest edges, and young tropical forests (reviewed by Schnitzer ).…”
Section: Discussionmentioning
confidence: 99%
“…In an examination of physiological traits of liana and tree saplings that were growing along roadsides in wet and seasonal forests in Panama, van der Sande et al. () reported that trees had the expected trade‐off between hydraulic conductance and hydraulic safety, whereas lianas did not, suggesting that lianas had the capacity to maintain high conductivity and thus high growth rates while resisting embolism. Collectively, these studies suggest that lianas are better able to grow during the dry season than co‐occurring trees, and thus are able to capitalize on high dry season light availability.…”
Section: Introductionmentioning
confidence: 99%
“…The proliferation of lianas appears to be driven by both higher survival and higher recruitment of lianas compared to trees, particularly in the first eight years of the study. Higher recruitment could reflect a past increase in liana seed production, while both higher recruitment and survival likely reflect a potential physiological advantage that allows liana seedlings to establish and survive better than tree seedlings (van der Sande et al, ). Despite the hypothesized effects of water availability and canopy gaps in driving the increasing prevalence of lianas, we did not find differences in demography between liana and tree seedlings related to habitat type, nor any relationship between changes in liana seedling relative abundance and annual rainfall, dry season length or proportion of area in gaps.…”
Section: Discussionmentioning
confidence: 99%
“…An evolutionary trade‐off between xylem water transport efficiency and xylem hydraulic and mechanical safety has been proposed to explain interspecific differences in drought resistance (Baas, Ewers, Davis, & Wheeler, ; Chave et al, ). However, recent studies show that generally, there is a weak trade‐off between hydraulic safety and efficiency, with many species showing both a low hydraulic safety and low hydraulic efficiency (Gleason et al, ; van der Sande, Poorter, Schnitzer, Engelbrecht, & Markesteijn, ). These findings limit the generalization and broader implementation of the safety‐efficiency trade‐off hypothesis in modeling frameworks and illustrate that the underlying mechanisms driving interspecific differences in drought resistance are still poorly understood in highly diverse tropical forests.…”
Section: Introductionmentioning
confidence: 99%